THE EFFECT OF PINEAPPLE PEEL EXTRACT (Ananas comosus L Merr) ON DRINKING WATER ON THE PHYSICAL QUALITY OF JOPER CHICKEN MEAT - A., Edison; Sriyani, N.L.P.; Ariana, I N.T. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study aims to determine the effect of giving pineapple peel extract on drinking water on the physical quality of joper chicken meat. The design used was a complete randomized design (RAL) with 4 treatments and 5 repeats so that there were 20 experimental units. Each tes consists of 3 joper chickens aged 2 weeks and a total of 60 joper chickens used. The treatments were P0 (joper chicken given drinking water without pineapple peel extract as a control, P1 (joper chicken given drinking water with 6% pineapple peel extract), P2 (joper chicken given 8% pineapple peel extract) and P3 (joper chicken given 10% pineapple peel extract). The variables observed were the physical quality of meat covering (pH, water tie, cooking shrinkage and raw shrinkage). The results showed that giving pineapple peel extract as much as 6%-10% had no real effect (P>0.05) on the physical quality of joper chicken meat. Based on the results of this study, it can be concluded that giving pineapple peel extract as much as 6%-10% has not been able to improve the physical quality of joper chicken meat.